2015
DOI: 10.4314/tjpr.v14i10.29
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits of Theanine in Green Tea: A Review

Abstract: Theanine is an amide exclusively present in tea and some fungi, and is an important bioactive component of tea. The bioactive effects of theanine include antitumour, anti-diabetic, antihypertensive, anti-stress activities, and the ability to improve cardiovascular and cerebrovascular diseases. It also has protective effect on nerve cells against damage induced by environmental neurotoxins as well as on liver from injury induced by excessive alcohol intake. The bioactive functions of theanine as well as its pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The content of amino acids (Pearson’s correlation was 0.867, p < 0.01) and theaflavins (Pearson’s correlation was 0.729, p < 0.01) was found to be highly significant with HUVEC cell survival rate. Amino acid was reported to have the ability of preventing nerve cell damage or death due to oxidative stress (Liang, Liu, Xiang, & Zheng, ), and theaflavins were reported to have neuroprotective effects against oxidative stress‐induced apoptosis in PC12 Cells (Zhang et al, ), and prevent cellular DNA damage by inhibiting oxidative stress (Feng et al, ) in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of amino acids (Pearson’s correlation was 0.867, p < 0.01) and theaflavins (Pearson’s correlation was 0.729, p < 0.01) was found to be highly significant with HUVEC cell survival rate. Amino acid was reported to have the ability of preventing nerve cell damage or death due to oxidative stress (Liang, Liu, Xiang, & Zheng, ), and theaflavins were reported to have neuroprotective effects against oxidative stress‐induced apoptosis in PC12 Cells (Zhang et al, ), and prevent cellular DNA damage by inhibiting oxidative stress (Feng et al, ) in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although caffeine is not considered as a polyphenolic compound, its capability to inhibit lipid peroxidation has been reported (Brezova et al, 2009 (Liang, Liu, Xiang, & Zheng, 2015), and theaflavins were reported to have neuroprotective effects against oxidative stressinduced apoptosis in PC12 Cells , and prevent cellular DNA damage by inhibiting oxidative stress (Feng et al, 2002) in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies in the literature focused on in vitro experiments in different subjects such as humans, cattle, pigs and rats. l-theanine reduces the toxic side effects associated with anticancer drugs, as well as lipid peroxidation and glutathione peroxidase enzyme activity induced by doxorubicin (DOX) drug, thereby ameliorating oxidative stress (Liang, Chang, Xiang, & Zheng, 2015;Zhang, Geng, Chen, Zhao, & Wang, 2019). The derivatives of l-theanine inhibit tumour growth by targeting vascular endothelial growth factor receptor-Akt/epidermal growth factor receptor/nuclear factor-kappa B (EGFR/VEGFR-Akt/NF-kappa B) signalling pathways which control cell proliferation and survival.…”
Section: Introductionmentioning
confidence: 99%
“…L-theanine (γ-glutamylethylamide; C 7 H 14 N 2 O 3 ) is a water-soluble, edible, non-proteinogenic amino acid found principally in Camellia sinensis, the source of green tea (1). Previous studies in rats have indicated that orally administered theanine is absorbed through the intestinal tract, and hydrolyzed to glutamic acid and ethylamine in the rat kidney (2,3).…”
Section: Introductionmentioning
confidence: 99%